The Importance of Linguistics for Teachers in English Language Teaching - Daulay, Sholihatul Hamidah; Dalimunte, Muhammad; Ningrum, Diah Widya (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
This writing aims to determine the function of Linguistics in English Language Teaching. It will discuss how important linguistics in English language teaching is. It uses the literature review method or called library research. In collecting the data, it uses the descriptive method and comparison method. From the finding, it can be concluded that linguistics pays attention to its function in teaching. Linguistics and language teaching are closely related to each other. This is because language teaching goes hand in hand with language growth. How is it possible that a language teacher can practice language skills if he does not master linguistics itself, how can he train writing skills if he does not master spelling, morphology, syntax, semantics, and lexicology? In addition, as a language teacher, he not only has to practice language skills but also has to explain the rules of the language correctly.